EP305 Rhabdomyosarcoma (RMS) of the uterine collar by the way of a case. (1st November 2019) - Hadjarab, F; Chekman, CE; Taibi, A; Bouzid, K
Abstract : Introduction/Background: Rhabdomyosarcoma (RMS) of the uterine collar is a rare tumour. It electively occurs atthe young woman. So formerly one preachedan aggressive surgical treatment goinguntil the pelvic exenteration, one currentlyrecommends a preserving treatmentsometimes limited to a conisation, associatedwith L chemotherapy has and whose resultsare encouraging. Methodology: Miss FN 19 years old, without pathologicalantecedents having regular menstruationssince the 13 years age followed since 2014 for rhabdomyosarcome of the uterine collar, marked by protrusion through the vagina of anoperated mass has 4 recoveries exerese typeexteriorized part whose histological study wasin favour of a rhabdomyosarcome embryonicbotriode type keeps II. The therapeutic decision of the multi-fieldcommittee was to make a chemotherapy first has standard 8 IVAO (Ifosfamide, Mesna, Vincristine, Doxorubicine. Results: Answer is considered to be partial with a tumoral weightsaving, disappearance of necroses as well as the haemorrhage it profited from an ovarian transposition by coelioscopy, then a exérèse of the mass (pédiculée of the uterine collar of 5 cm and been confined by the vagina) by gynaecological way, whose anapath was in favour of cervical Rhabdomyosarcome with healthy zones ofresection the treatment was continued by acuriethérapie (4 fractions) in March 2016. Currently in August 2016, the patient is incomplete remission with a pelvic scannerthoraco abdomino and MRI pelvic of evaluationwithout characteristic and it had a return of themenstruations in May 2016. Conclusion: The RMS of the uterine collar is a rare tumor which occurs primarily in the young girl. The extension is especially loco régionale. The treatment consists of a surgical gesture with minima associated with an perish-operational chemotherapy. Disclosure: No any conflict.